Pengembangan Masyarakat di Kota Cirebon Melalui Kerjasama Pemerintah dengan Industri Media Digital - Anwar, Rully Khairul; Rizal, Edwin (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
This study explored the role of government to encourage and provide a model of economic growth, including in the field of micro, small, and medium enterprises. Among these was the digital media industry. It could be a potential that can provide public welfare. The questions to be answered here were about how to model a development of community-based digital media industry in Cirebon City, West Java; whether the government could bring people to the digital media industry in order to foster the creative economy of society; and how the community appreciated and became a part of the digital media industry. With descriptive and qualitative methods, this study found that the government had sufficiently active roles in the development of the digital media industry in the community. The community itself had already been opened in responding to the government’s programs and the development of contemporary technology in the field of selling goods and services. Still, there were obstacles that might be continued to be refined for the success of the community’s digital media industry.